Intergenerational caregiving on mental health of middle-aged and older adults in China: empirical insights - Xueling Yan; Wenjing Wu; Xiaoqin Chen; Guangming Xu; Shule Yu; Shen Li (Frontiers Media S.A., 2023)
IntroductionThe impact of intergenerational caregiving on the mental health of providers remains a controversial topic, especially in countries like China where it is prevalent. Given the country's aging population and recent liberalization of the two-child policy, understanding the effects of intergenerational caregiving on the mental health of middle-aged and older adult(s) individuals is crucial. This study aimed to explore the impact of intergenerational caregiving on mental health among middle-aged and older adult(s) individuals.MethodsWe analyzed data from the China Health and Aging Tracking Survey (CHARLS) 2013, consisting of 6602 participants finally. Personal information, family structure, financial support, health status, and physical measurements were selected for analysis. Correlation and regression analyses were used for relationships among variables controlling for potential confounding variables. Mental health status was evaluated using the depression self-rating scale.ResultsThere is a significant positive effect of intergenerational care on the mental health of middle-aged and older adult(s) people. Additionally, we re-profiled intergenerational care variables by considering the number and length of intergenerational caregivers, and found that the effects remained significant. Furthermore, the effects of intergenerational care vary across subgroups based on gender, age, nature of usual residence, marital status, and physical health status. Finally, we identified two mechanisms through which intergenerational caregiving positively affects mental health: intergenerational financial support and intergenerational spiritual support.DiscussionThese findings have important implications for policymakers, healthcare professionals, and family members in promoting the mental health of middle-aged and older adult(s) individuals in China.